Damping Characteristic Analysis of LCL Inverter with Embedded Energy Storage - Jingbo Zhao; Yongyong Jia; Guojiang Zhang; Haiyun An; Tianhui Zhao (Energies, 2025)
This paper investigates the system architecture and circuit topology of grid-connected inverters with embedded energy storage (EES), encompassing their modulation strategies and control methodologies. A mathematical model for an EES grid-connected inverter is derived based on capacitor current feedback control, from which the expression for the inverter’s output impedance is obtained. Building on this foundation, this study analyzes the influence of control parameters—such as the proportional coefficient, resonant coefficient, and switching frequency—on the inverter’s output impedance. Subsequently, the stability of single and multiple inverter grid-connected systems under various operating conditions is assessed using impedance analysis and the Nyquist criterion. Finally, the validity of the stability analysis based on the established mathematical model is verified through simulations conducted on the Matlab/Simulink platform, where models for both a single inverter and a two-inverter grid-connected system are constructed.